Isolating and studying the effect of natural products isolated from the Alhagi maurorum Medik on the level of sirtuin7 and some biochemical variables in mice with cardiovascular diseases - Hiba Nasser Lazem Al-Nasiri, Mohammed Bahry Hassin Al-Sadoon (South Eastern European Journal of Public Health, 2025)
The study included the isolation and diagnosis of various natural products from Aqul. The oily substance, its fatty acids, and the flavonoid compounds were isolated and diagnosed by means of high performance liquid chromatography. Also, alkaloids were isolated. It was observed that the products elevated the level of enzyme sirtuin7, and it positively reflected along with their positive effects on all other measured biochemical variables. It also checked the influence of these products on some biochemical variables related to the cardiovascular disease in the serum of the diseased mice. Among these biochemical variables were sirtuin7 (SIRT7), tumor necrosis factor-alpha (TNF-a), glutathione peroxidase (GPx), glutathione (GSH), and malondialdehyde (MDA). For example, the level of SIRT7, GPx, and GSH significantly decreased in the infected mice compared to healthy mice, while TNF-a and MDA levels showed.